Comparative evaluation of antioxidant activity, total phenolic content, anti-inflammatory, and antibacterial potential of Euphorbia-derived functional products - Benjamaa, Rania; Elbouny, Hamza; Errati, Hajare; Moujanni, Abdelkarim; Kaushik, Neha; Gupta, Ravi; Ennibi, OumKeltoum; Nasser, Boubker; Choi, Eun Ha; Kaushik, Nagendra Kumar; Essamadi, Abdelkhalid (Frontiers in Pharmacology, 2024)
This study assessed the medicinal properties of Euphorbia resinifera O. Berg (E. resinifera) and Euphorbia officinarum subsp echinus (Hook.f. & Coss.) Vindt (E. echinus, known for their pharmaceutical benefits. Extracts from their flowers, stems, propolis, and honey were examined for phenolic content, antioxidant, anti-inflammatory, and antibacterial activities. Total polyphenolic content (TPC), total flavonoid content (TFC), and total condensed tannin (TCC) were determined using specific methods. Antioxidant potential was assessed through various tests including DPPH, FRAP, ABTS, and TAC. Anti-inflammatory effects were evaluated using phenol-induced ear edema in rats, while antibacterial activity was measured against Gram-positive (S. aureus ATCC 6538) and Gram-negative (E. coli ATCC 10536) bacteria.Among the extracts, the aqueous propolis extract of E. resinifera demonstrated exceptional antioxidant capabilities, with low IC50 values for DPPH (0.07 ± 0.00 mg/ml) and ABTS (0.13 ± 0.00 mg/ml), as well as high TAC (176.72 ± 0.18 mg AA/mg extract) and FRAP (86.45 ± 1.45 mg AA/mg extract) values. Furthermore, the anti-inflammatory effect of E. resinifera propolis extracts surpassed that of indomethacin, yielding edema percentages of 3.92% and 11.33% for the aqueous and ethanolic extracts, respectively. Microbiological results indicated that the aqueous extract of E. resinifera flower exhibited the most potent inhibitory action against S. aureus, with an inhibition zone diameter (IZD) of 21.0 ± 0.00 mm and a minimum inhibitory concentration (MIC) of 3.125 mg/ml. Additionally, only E. resinifera honey displayed the ability to inhibit E. coli growth, with an IZD of 09.30 ± 0.03 mm and a MIC of 0.0433 mg/ml.